STUDY ON THE DETAILED DESIGN OF INTERIOR SPACE USING COPPER MATERIALS - Li Yanlin; Haslinda Abd. Razak; Liza Marziana Mohammd Noh (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
This paper will focus on the application of copper materials and artistic expression techniques in the detailed design of interior spaces, and take the detailed performance of copper materials in interior design as an entry point to analyze the cultural and aesthetic value of copper detailing in interior space design, to explore in depth the artistic expression of copper materials in the detailed design of interior spaces. The study and exploration of the rich connotation and expression of copper as an interior space design material, and the exploration of the deeper artistic expression of copper in detail design, to provide a broader range of ideas and vision for the better application of copper materials in the detail design of interior spaces. This paper is based on the language and extensive practical application of copper materials, using a combination of theory and practice, and a method of subjective and objective argumentation.The detailed design is analyze in terms of the purity and comprehensive performance of copper materials in the design of interior spaces. Taking the design of copper detailing as an example to dig deeper into the logic of thinking when the material intervenes in the construction of contemporary interior space detailing design. Based on the theoretical overview and the analysis of actual cases, the theoretical system of interior design theory is further improved by taking copper as an example to create detailing with materials, and by using detailing as a prototype for spatial design, and by summarizing the corresponding design strategies and methods for creating detailing with materials.